School inclusion: possible contributions of physical therapy from the perspective of teachers - Santos, Marcelli Evans Telles dos (2014)
The school enrollment has caused debate among professionals in education and health. In this context, the participation of the physiotherapist can help the students to develop their potential in school. However, this area is little explored and the work regarding the role of the physiotherapist as an integral member of a school support group that performs the inclusion of pupils with special education needs still is restricted. Therefore, this study has aimed at investigating the perceptions of professionals working in resource rooms, in relation to the possible contributions of physical therapy in school inclusion and meet the main difficulties faced by these professionals. Study participants were eight teachers from three state schools in Uruguaiana-RS. The instrument used was a semi-structured interview, which was conducted individually, recorded and later transcribed for analysis. The collected data were analyzed according to Bardin ́s content analysis (2004). The results show that the respondents have a positive view regarding the inclusion of physical therapy school, as they recognize its importance and also have knowledge about the possible forms of contribution in this context. In view of the reports it was concluded that there are possibilities of physical therapy contributing to the inclusion of school and there is also the need for the physiotherapist to disseminate knowledge about the performance for the university community and school.